1992
DOI: 10.3354/meps081121
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of dissolved silicate in Chesapeake bay: implications for the production and fate of phytoplankton biomass

Abstract: Seasonal variations in the distribution of dissolved inorganic nitrogen, sihcon, and phosphorus along the salinity gradient of Chesapeake Bay from 1984 to 1988 suggest that dissolved silicate (DSi) controls the magnitude of diatom production during the spring bloom, causes the collapse of the spring bloom, and leads to changes in floristic composition. High sedimentation rates of chlorophyll biomass observed during this per~od could be due to Si-deficiency, suggesting that the supply of DSi may also control th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
1
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(121 citation statements)
references
References 24 publications
4
107
1
6
Order By: Relevance
“…These features seem to be a regular feature of Nenriched ecosystems. The same result is reported in the Chesapeake Bay (Conley and Malone, 1992;D'Elia et al, 1992;Fisher et al, 1998). In spring, D 'Elia et al (1992) observed a potential P-limitation with rapid turnover rates for phosphate, while in summertime, the ratios fall well below the level at which potential N-limitation can occur.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These features seem to be a regular feature of Nenriched ecosystems. The same result is reported in the Chesapeake Bay (Conley and Malone, 1992;D'Elia et al, 1992;Fisher et al, 1998). In spring, D 'Elia et al (1992) observed a potential P-limitation with rapid turnover rates for phosphate, while in summertime, the ratios fall well below the level at which potential N-limitation can occur.…”
Section: Discussionsupporting
confidence: 76%
“…In the same way, several studies have highlighted the hypothesis of Si-limitation for diatom growth in nitrate-rich coastal waters (Schelske and Stoermer, 1971;Schelske and Stoermer, 1972;Officer and Ryther, 1980;Smayda, 1989;Smayda and White, 1990;Maestrini and Graneli, 1991;Conley and Malone, 1992;Egge and Aksnes, 1992;Rabalais et al, 1996;Rahm et al, 1996). It is believed to cause a shift in species composition which may result in harmful phytoplankton blooms (Schelske and Stoermer, 1972;Smayda, 1989;Smayda and White, 1990;Maestrini and Graneli, 1991;Egge and Aksnes, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…An example is the Chesapeake Bay where dissolved silicate concentrations and loading determine the magnitude of the diatom bloom during the spring, causes the collapse of the spring diatom bloom and leads to changes in floristic composition of phytoplankton communities (Conley & Malone, 1992) allowing for diatoms to be replaced by species not requiring dissolved silicate for growth. In the Bay of Brest, dissolved silicate limitation appears to be a relatively recent phenomena first observed in the 1990s, whereas prior to this time the Bay of Brest was primarily N limited (Del Amo et al, 1997).…”
Section: Nutrient Limitationmentioning
confidence: 99%
“…Nitrogen (N), phosphorus (P) and silica (Si) are essential elements controlling primary production in estuarine environments (Ryther & Dunstan 1971, Howarth 1988, Conley & Malone 1992. These cycles are interrelated by organic matter production and decomposition.…”
Section: Introductionmentioning
confidence: 99%